Encyclopedia of Turkey (New York)
[vii], 313 s.
Keywords: "This encyclopedia presents important research on Turkey. Some of the topics discussed herein include the prospects and challenges involved in Turkey and United States defense cooperation; Turkey-Kurdish regional government relations after the U.S. withdrawal from Iraq; Turkey's new regional security role's implications for the U.S.; and Turkey's background and relations with the United States." --